2020
DOI: 10.1007/s00018-020-03475-1
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitin ligands: a growing armamentarium to tackle cancers, osteoporosis, inflammatory, cardiac and neurological diseases

Abstract: Over the last three decades, the scaffold proteins prohibitins-1 and -2 (PHB1/2) have emerged as key signaling proteins regulating a myriad of signaling pathways in health and diseases. Small molecules targeting PHBs display promising effects against cancers, osteoporosis, inflammatory, cardiac and neurodegenerative diseases. This review provides an updated overview of the various classes of PHB ligands, with an emphasis on their mechanism of action and therapeutic potential. We also describe how these ligands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 116 publications
0
50
0
Order By: Relevance
“…PHBs interact with a multitude of signaling proteins, such as the kinases C-RAF (RAF1), Akt, IKK, MLK2, AMPK, the phosphatase Shp1/2, the scaffold proteins 14-3-3 and BIG3, histone deacetylases, the histone N -methyltransferase EZH2, the transcription factors STAT3, E2F, p53, HES1, RNF2, Rb, and the estrogen receptor to cite few examples. 7 …”
Section: Prohibitins and Their Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…PHBs interact with a multitude of signaling proteins, such as the kinases C-RAF (RAF1), Akt, IKK, MLK2, AMPK, the phosphatase Shp1/2, the scaffold proteins 14-3-3 and BIG3, histone deacetylases, the histone N -methyltransferase EZH2, the transcription factors STAT3, E2F, p53, HES1, RNF2, Rb, and the estrogen receptor to cite few examples. 7 …”
Section: Prohibitins and Their Ligandsmentioning
confidence: 99%
“…Several classes of mammalian PHB ligands have been discovered and shown to display diverse profiles of pharmacological activities, suggesting that they stabilize different conformations of PHBs. 7 The most studied class of PHB ligands are natural compounds called flavaglines found in trees used in traditional Chinese medicine. Most of the other types of PHBs ligands are small synthetic molecules identified in phenotypic screenings.…”
Section: Introductionmentioning
confidence: 99%
“…Prohibitins-1 and -2 (PHB1/2) are evolutionary conserved scaffold proteins that control a myriad of signaling pathways [ 41 ]. The multiple functions of PHBs are regulated not only by phosphorylation at different positions by Akt, Cam kinase IV, Aurora A, protein kinase C (PKC), Lyn and insulin receptor, but also by N -myristoylation, palmitoylation, tyrosine nitrosylation and sulfatation, transamidation, arginine deamination and O -GlcNAc modifications.…”
Section: Antiviral Activities Of Flavaglines Mediated By Prohibitinsmentioning
confidence: 99%
“…In contrast to the role of eIF4A in viral replication [ 19 ], the implication of PHBs in viral replication has not yet been reviewed. Several families of small molecules targeting PHBs, including flavaglines, have been shown to display promising activities in some animal models of cancers, osteoporosis, inflammation, cardiac and neurodegenerative diseases [ 41 ], and also some viral infections, notably for inhibiting viral entry.…”
Section: Antiviral Activities Of Flavaglines Mediated By Prohibitinsmentioning
confidence: 99%
“…It was shown that in urothelial carcinoma cells, FL3 can directly binds to Prohibitin 1 (PHB) preventing its phosphorylation by Akt, leading to a decrease of PHB in mitochondria, which causes a mitochondria-related apoptosis and cell cycle inhibition 5 , 6 . PHB is an ubiquitous and evolutionarily conserved protein expressed in different cellular compartments including the nucleus, cytoplasm and mitochondria 7 , it is involved in diverse biological processes such as cell proliferation, resistance to apoptosis, maintenance and integrity of mitochondria 7 , 8 . Also, FL3 was shown to selectively kill cancer stem-like cells through the p38 mitogen-activated protein kinase (MAPK)-dependent caspase-3-dependent pro-apoptotic pathway, without being toxic to normal stem-like cells 9 .…”
Section: Introductionmentioning
confidence: 99%